Les representations architecturales dans l'iconographie Neo-Assyrienne - Gillmann, Nicolas. (Culture and History of the Ancient Near East, 2016)
In this book Nicolas Gillmann provides scholars as well as non-specialists with a comprehensive study of architectural representations in Neo Assyrian iconography. The author answers three important questions: How are Mesopotamian images conceived? What rules are presiding over them and how are they to be interpreted by modern viewers? Can the architectural representations be of some use to archaeologists or are they merely schematic depictions of given building types? Nicolas Gillmann shows that new conclusions can be reached once the reader is given the right reading keys and interpretation framework.